Pengaruh Penggunaan Aplikasi Quizizz terhadap Efektivitas Pembelajaran Pendidikan Agama Islam - Nuramanah, Syifa Agestrisna; Iwan, Cecep Darul; Selamet, Selamet (Bestari, 2020)
This study aims to: 1) determine how to use the Quizizz application at SDN 3 Cisaga, 2) find out how the effectiveness of Islamic Education learning at SDN 3 Cisaga, 3) determine whether there is an effect of using the Quizizz application on the effectiveness of Islamic Education learning at SDN 3 Cisaga. This research is a quantitative research with an experimental approach, the population in this study is the upper class (class 4, 5 and 6) at SDN 3 Cisaga, amounting to 56 people, while the sampling technique uses stratifield random sampling technique which is used as the entire population as a sample if the population less than 100. Which means, the sample was taken as a whole with a total of 56 people. Data collection was done by using a questionnaire technique. The data analysis technique used is inferential statistical analysis, independent analysis of the sample T test. The results of this study indicate that: 1) The use of the Quizizz application is in moderate qualification by reaching an average value of 80.17, this indicates that the use of the Quizizz application is in the range of 75.86 to 84.46. 2) The effectiveness of Islamic Education Learning is in moderate qualification as well as reaching an average value of 83.75, this shows that the effectiveness of Islamic Education Learning is in the range of 81.08 to 86.40. 3) The use of the Quizizz application has an influence on the effectiveness of Islamic Education learning, this is indicated by the calculations that have been carried out by researchers, from the calculation results obtained through the significant test of the correlation coefficient at the 5% significance level obtained tcount> ttable (8.132> 2.004) and the sig or probability <0.05 (0.000 <0.05), indicating that statistically the use of the Quizizz application has a significant effect between learning using the Quizizz application on the effectiveness of PAI learning so that Ho is rejected and Ha is accepted.